Response of brassinosteroids to nitrogen rates and their regulation on rice spikelet degeneration during meiosis. (4th March 2020) - Zhang, Weiyang; Fu, Lidong; Men, Chuanbao; Yu, Jixiang; Yao, Jiayu; Sheng, Jiayan; Xu, Yunji; Wang, Zhiqin; Liu, Lijun; Yang, Jianchang; Zhang, Jianhua
Abstract: The plant steroid hormones brassinosteroids (BRs) play pivotal roles in modulating flower and fruit production. Nitrogen (N) is a key factor affecting rice ( Oryza sativa L.) production. We hypothesized that BRs would respond to N application rates at spikelet differentiation (SD) and regulate spikelet degeneration in rice. Three rice cultivars were field‐grown and treated with five N rates at SD. Plant N and BRs contents, antioxidant capacity, and energy status were observed during meiosis in young panicles, and their relationships with spikelet degeneration were evaluated. In all the N treatments, the BRs, adenosine triphosphate, and energy charge levels, activities of the enzymes involved in energy metabolism, including cytochrome C oxidase and succinate dehydrogenase, total antioxidant capacity, and grain yield, were the highest, whereas hydrogen peroxide (H2 O2 ) content and vacuolar processing enzymes (VPE) genes expression levels, and spikelet degeneration rate were the lowest when plant N content was 2.6% during meiosis. The rice BRs‐deficient mutants showed substantial reduction in BRs levels, antioxidant capacity, and energy status, but great increase in H2 O2 content, VPE genes expression levels, and spikelet degeneration rate than the wild type (WT); moreover, these parameters in WT panicles could be regulated, whereas in BRs‐deficient mutant panicles, they were not distinctly affected by N application. The results indicated that BRs mediate the effects of N rates on spikelet degeneration, and elevated BRs levels in rice panicles effectively inhibit spikelet degeneration when plant N content is 2.6% during meiosis by elevating antioxidant capacity and energy status. Abstract : Increased brassinosteroids (BRs) contents in young rice panicles during meiosis could decrease spikelet degeneration rate. A plant nitrogen (N) content is 2.6% during meiosis could enhance BRs levels in the young panicles and reduce spikelet degeneration of rice. BRs mediate the effects of N application rates on the rice spikelet degeneration through regulating the antioxidant capacity and energy status in the panicles during meiosis.